Glifosato: Propriedades, toxicidade, usos e legislação - De Amarante Junior, Ozelito Possidônio; Dos Santos, Teresa Cristina Rodrigues; Brito, Natilene Mesquita [UNESP]; Ribeiro, Maria Lúcia [UNESP] (FapUNIFESP (SciELO), 2002)
This paper supplies a compact revision on the herbicide glyphosate physic-chemistry characteristic mains, including toxicity and valid Brazilian legislation for its use.
Glyphosate: Properties, toxicity, use and legislation
Keywords: Glyphosate; Legislation; Physic-chemistry characteristic; Toxicity; glyphosate; herbicide; Brazil; degradation; law; microbiology; nonhuman; review; toxicity